2004
DOI: 10.5194/angeo-22-1613-2004
|View full text |Cite
|
Sign up to set email alerts
|

Energy distribution of precipitating electrons estimated from optical and cosmic noise absorption measurements

Abstract: Abstract. This study is a statistical analysis on energy distribution of precipitating electrons, based on CNA (cosmic noise absorption) data obtained from the 256-element imaging riometer in Poker Flat, Alaska (65.11 • N, 147.42 • W), and optical data measured with an MSP (Meridian Scanning Photometer) over 79 days during the winter periods from 1996 to 1998. On the assumption that energy distributions of precipitating electrons represent Maxwellian distributions, CNA is estimated based on the observation dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…The imaging riometer scans an antenna beam in about 200 directions within 1 s to monitor cosmic radio noise variation at 38.2 MHz over a wide field of view of the radio sky. It observes lower ionospheric disturbances over a 400‐km by 400‐km field of view at the 90‐km height with a spatial resolution of about 7° (11 km around the zenith), a sensitivity better than 0.1 dB, and a time resolution of 1 s [ Murayama et al , 1997; Mori et al , 2004].…”
Section: Experimental Techniquementioning
confidence: 99%
“…The imaging riometer scans an antenna beam in about 200 directions within 1 s to monitor cosmic radio noise variation at 38.2 MHz over a wide field of view of the radio sky. It observes lower ionospheric disturbances over a 400‐km by 400‐km field of view at the 90‐km height with a spatial resolution of about 7° (11 km around the zenith), a sensitivity better than 0.1 dB, and a time resolution of 1 s [ Murayama et al , 1997; Mori et al , 2004].…”
Section: Experimental Techniquementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Plasmas with an excess of superthermal ͑non-Maxwellian͒ electrons are generally characterized by a long tail in the high energy region. [1][2][3][4][5][6][7][8][9][10][11] Plasmas with an excess of superthermal ͑non-Maxwellian͒ electrons are generally characterized by a long tail in the high energy region.…”
Section: Introductionmentioning
confidence: 99%
“…The energy spectra were estimated with a kappa distribution for the case of δ CNA > 0 [cf. Mori et al , 2004] and a Gaussian distribution for the case of δ CNA < 0 [cf. Ono and Hirasawa , 1992] because they were often used to represent the spectra for the diffuse aurora and for the discrete aurora, respectively.…”
Section: Observational Resultsmentioning
confidence: 99%
“…For instance, the ratio of CNA to the auroral (557.7‐nm) intensity has been used as an indicator of electron energy spectrum hardening [ Ansari , 1964; Johansen , 1965; Berkey , 1968]. Recently, Mori et al [2004] compared CNA observed with an imaging riometer with theoretical values estimated from meridian scanning photometer data and demonstrated that kappa or double‐Maxwellian energy distributions explain the observed CNA better than a Maxwellian does. Their results indicate that CNA can be used to estimate the energy spectra, including the high‐energy range.…”
Section: Introductionmentioning
confidence: 99%